2022
DOI: 10.2528/pierc22010608
|View full text |Cite
|
Sign up to set email alerts
|

A New Broadband Antenna of High Gain: The Double-Cornu Spiral Antenna

Abstract: A new planar compact antenna composed of two crossed Cornu spirals is presented. Each Cornu spiral is fed from the center of the linearly part of the curvature between the two spirals, which builds the clothoid. Sequential rotation is applied using a sequential phase network to obtain circular polarization and increase the effective bandwidth. Signal integrity issues have been addressed and designed to ensure high quality of signal propagation. As a result, the antenna shows good radiation characteristics in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The discrepancies observed around 22 GHz are due to the fabrication tolerances regarding the connector soldering. Furthermore, it was observed that the connector-fed array exhibits a broadened AR about 1 GHz compared to the AR of the fabricated single DCSA [1]. However, it is worth mentioning that the 3-dB bandwidth of the array of DCSA at the broadside and all azimuth angles is very similar to that of the single DCSA [1].…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…The discrepancies observed around 22 GHz are due to the fabrication tolerances regarding the connector soldering. Furthermore, it was observed that the connector-fed array exhibits a broadened AR about 1 GHz compared to the AR of the fabricated single DCSA [1]. However, it is worth mentioning that the 3-dB bandwidth of the array of DCSA at the broadside and all azimuth angles is very similar to that of the single DCSA [1].…”
Section: Resultsmentioning
confidence: 82%
“…The designed antenna according to Fig. 3 an in-house made far-field antenna measurement system consisting of a full-anechoic chamber operating from 3 to 80 GHz, a linearly polarized standard gain horn antenna, with a constant gain of 13 dB from 17 to 34 GHz, and a network analyzer (RαS ZNB) [1]. The measurement step was 50.0 MHz for frequencies and 5 • for the elevation angle.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations